21. ROTATOR CUFF REPAIR AND ALLOGRAFT ACELLULAR DERMAL MATRIX AUGMENTATION: RISK OF FAILURE MINIMALIZATION IN REPAIRABLE LARGE-MASSIVE ROTATOR CUFF TEAR WITH HIGH-GRADE FATTY INFILTRATION?- SHORT-TERM EVALUATION (Vietnam Journal of Community Medicine, 2024)
Introduction: Large-massive rotator cuff tears (RCT) with high-grade fatty infiltration (HGFI) are challenging cases. In repairable tears, the failure rate is often high (34-94%). Patch augmentation with autografts or allografts may reduce this rate.Population and methods: We retrospectively evaluated 6 cases of large-massive RCT with HGFI (Goutallier grade 3-4) were operated on with hybrid or double-row sutures, augmented with an allograft acellular dermal matrix (ADM). Constant and ASES scores were recorded before surgery, at 3 months, and 6 months post-surgery. MRI was performed 2 weeks and 6 months after surgery.Results: Age ranged from 59-73 years, BMI from 22.3-26.4 kg/m², with an average follow-up of 7.2 months (6.2-9 months). The average preoperative ASES and Constant scores were 28 (14-54) and 42 (36-70) respectively, and at 6 months they were 72 (60-94) and 74 (70-91) respectively. No failures have been recorded.Discussion: The failure rate is usually high as 34-94%; double-row and hybrid sutures might reduce the failure rates. Patch augmentation with grafts reduces this rate to 12.5-20%. The failure rate and functional outcomes are similar between autografts and allografts. However, some complications can occur at the donor site of autograft harvesting.Conclusion: Rotator cuff repair and patch augmentation with an allograft ADM could be an effective method to minimize the re-tear rate in cases of large-massive RCT with HGIF.